The modernization of cil law institutions : civil liability, property and contract - Woolcott Oyague, Olenka, (Colección Jus privado ;, 2019)
This work analyzes the treatment and contributions of Latin American las to specifics problems that are the object of continuous discussion in the doctrine and jurisprudence. To this end, the authors identify as principal issues of concerns: strict liability for hazardous activities in Colombian jurisprudence and in European tort law, the methods of property trasnfer of merchandise in international trade, and contract withdrawal in European and American civil codes.